Does exiting a company whatsapp group justify dismissal?: a review of Thilagavathy A/P Arunasalam V Maxis Mobile Sdn Bhd - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2019)
The issue whether exiting or quitting the company’s WhatsApp group without prior permission of the superior constitutes a misconduct that warrants discipline is discussed in this article with reference to the recent Industrial Court’s award in Thilagavathy A/P Arunasalam v Maxis Mobile Sdn Bhd. In this case, the Industrial Court held, inter alia, that the claimant’s action of exiting the WhatsApp group created by the superior without his prior permission is an act of insubordination as it violates the express instructions of her superior. The real issue however is whether a single act of misconduct as above justifies dismissal? If the answer is in the affirmative, then the issue is whether the claimant’s act of exiting the company’s WhatsApp group was such that ‘it goes to the root of the contractual relation of master and servant so as to indicate unwillingness on the part of the servant to be bound upon his original terms of contract.’